2018
DOI: 10.1101/408823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards understanding cancer stem cell heterogeneity in the tumor microenvironment

Abstract: The Epithelial-Mesenchymal Transition (EMT) and Cancer Stem Cell (CSC) formation are two paramount processes driving tumor progression, therapy resistance and cancer metastasis. Some recent experiments show that cells with varying EMT and CSC phenotypes are spatially segregated in the primary tumor. The underlying mechanisms generating such spatiotemporal dynamics and heterogeneity in the tumor micro-environment, however, remain largely unexplored. Here, we show through a mechanism-based dynamical model that t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…Our earlier efforts at quantifying the association between EMT and stemness have predicted that cells in hybrid E/M states are more inclined to gain stem-like properties [27,42,43], a prediction that has been recently validated in vitro and in vivo [2, 44,45]. Reinforcing these predictions, NRF2 has been related to cancer stem-like traits and chemo-resistance [35].…”
Section: Discussionmentioning
confidence: 89%
“…Our earlier efforts at quantifying the association between EMT and stemness have predicted that cells in hybrid E/M states are more inclined to gain stem-like properties [27,42,43], a prediction that has been recently validated in vitro and in vivo [2, 44,45]. Reinforcing these predictions, NRF2 has been related to cancer stem-like traits and chemo-resistance [35].…”
Section: Discussionmentioning
confidence: 89%
“…Previous efforts to couple EMT with intercellular signaling have disregarded the loss of cell-cell adhesion leading to a reduced cell-to-cell signaling between mesenchymal cells (58). Also, we recently showed that JAG1, a Jagged ligand subtype, promotes the growth of tumor organoids in breast cancer cells in vitro (12). Overall, these observations suggest that Jagged can facilitate a 'plasticity window' that maximizes tumor aggressiveness in terms of EMT, proliferation and therapeutic resistance (45).…”
Section: What Molecular Mechanisms Can Maximize the Metastatic Potentmentioning
confidence: 78%
“…This replacement represents the turnover of cancer cells, owing to their enhanced proliferation potential, that may also reach the periphery of the tumor. In fact, cells at the periphery of a tumor can be more exposed to EMT-inducing signals whereas cells in the interior exhibit more epithelial traits (11,12).…”
Section: A Percolation Model With Escape To Couple Epithelial-mesenchmentioning
confidence: 99%
“…Furthermore, this model proposed a strong overlap between a hybrid E/M phenotype, CSC properties and Notch-Jagged signaling [13], a pathway implicated in both drug resistance and in clusters of CTCs, the key drivers of metastasis [33]. Consistently, knockdown of Jagged was shown to restrict the growth of tumor emboli in SUM149 inflammatory breast cancer cells [82]. Given the role of Notch signaling in pattern formation in multiple contexts [83,84], Notch signaling coupled with EMT circuitry may underlie the spatial segregation of different subsets of cells with stem-like traits, as observed experimentally in a breast cancer tissue [85].…”
Section: Towards An Integrated Understanding Of Emt and Cscmentioning
confidence: 87%
“…Given the role of Notch signaling in pattern formation in multiple contexts [83,84], Notch signaling coupled with EMT circuitry may underlie the spatial segregation of different subsets of cells with stem-like traits, as observed experimentally in a breast cancer tissue [85]. Secretion of a diffusive EMT-inducing signal at the tumor-stroma interface (such as TGF-), along with cell-cell signaling through Notch, was shown to give rise to mesenchymal CSCs at the invasive edge of the tumor and a population of hybrid epithelial/mesenchymal (E/M) CSCs in the tumor interior [82]. The idea that cell-cell signaling and the microenvironment can shape the spatial distribution of a cell population has been examined in different biological contexts, such as bacterial colonies [86,87] or eukaryotic chemotaxis [88,89], but remains largely unexplored in cancer biology, and thus demands further attention.…”
Section: Towards An Integrated Understanding Of Emt and Cscmentioning
confidence: 88%